Empowering Leadership and Voice Behavior: Mediation Role of Job Autonomy and Proactive Personality - Chairunnisa, Anida; Purba, Debora Elfina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
Previous research has proven a weak relationship between empowering leadership and Voice behavior indicating the existence of a psychological mechanism between the two variables. Using trait activation theory, this research aims to explore the role of work autonomy and proactive personality as serial mediators in the relationship between empowering leadership and Voice behavior.The data collection method was carried out using convenience sampling by distributing online questionnaires to respondents who work in biopharmaceutical technology and health-based companies (N = 155). Data analysis was carried out with SPSS version 25 software using Hayes' PROCESS Macro model 6. The results of the study showed the mediating role of work autonomy and proactive personality significantly and sequentially in the relationship between empowering leadership and Voice behavior. The implication of this research is the effectiveness of using Trait Activation Theory in explaining the psychological mechanisms of employee Voice behavior. The practical implications of this research are that organizations can provide training to managers to be able to implement empowering leadership so as to give employees the freedom to determine the way they work and activate personality traits that support Voice behavior in employees.